Responsibility of States About Pandemic COVID-19: International Law Review - Satria Unggul Wicaksana Prakasa; Lilik Puja Rahayu; Abrari Abrari; Muallimin Mochammad Sahid; Asri Wijayanti (Jurnal Hukum Novelty, 2022)
Introduction to The Problem: This research focused on analyzing responsibility of States about COVID-19 pandemic. The concept of international responsibility could be interpreted as a relation between the state sovereignty in national legal mechanism, and also implementation of the principles of the international law in the other sides to fix it about internationally wrongful act. Especially how states contribution to prevent, vaccines, prosperity/ social aid, and health services for people in its states.Purpose/Objective Study: This research would answer the following questions: (1). How the responsibility of states about COVID-19 pandemic under international law ?; (2). What is the dispute settlement mechanism for the fulfillment of international law? obligations by states?Design/Methodology/Approach: This research used socio-legal studies to identify between political, economy, and law approach to understanding what states responsibility regarding COVID-19 pandemic under international law.Findings: This article argued that strong relations regarding state responsibility in the face of international legal mechanisms, through international cooperation mechanisms as well as diplomatic approaches shall be prioritized, to identification regarding internationally wrongful act. Then the fulfilment of basic rights of citizens during COVID-19 pandemic such as access to health services, vaccines, and socio-economic consequences are responsible for the country. Parties that can sue the state in international liability can be from state actors and non-state actors. China as a based on Covid-19 are spread around the world are bears some international responsibility for the unquantifiable damage sustained as a direct result of the state having failed to contain the virus, and to notify the international community of its existence. Therefore, judicial mechanisms through the UN mechanism or outside the UN Mechanism to dispute settlement mechanism.Paper Type: Research Article